(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Water represents the most important and main component on the surface of our planet. It is a basic and essential necessity for all living things on Earth, including humans. As a result, water that humans drink needs to be safe, readily available, sufficient, and uncontaminated. Moreover, water pollution is a severe environmental problem that jeopardizes ecological sustainability, human health, and economic development. Due to natural and human activities, water has become contaminated with various types of polluted. Water pollution by factories, agriculture, and sewage can it make it unfit for human use and is harmful to the environment and causes negative impact on human health because it contains organic and inorganic pollutants. Therefore, humans must work to maintain water quality and treat polluted water. The present review aims to identify water pollution through the use of biological, chemical, and physical indicators. It also classifies water pollution according to their many sources, origins, and effects on human health. Additionally, a brief discussion on different technological used to treat water pollutant.